2018
DOI: 10.1039/c7sm02177a
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte multilayers under compression: concurrent osmotic stress and colloidal probe atomic force microscopy

Abstract: Colloidal interactions have been characterised using both osmotic stress and surface forces. Here these methods are employed concurrently to measure the interaction forces of polyelectrolyte multilayers that when cross-linked form a dextran impermeable membrane. The force data, corrected for the thickness of the polyelectrolyte multilayer film, has been expressed as pressure versus separation enabling the interaction from osmotic stress measurements to be compared to the measured interaction from the colloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Results and Discussion. In our procedure, we have recorded SFG spectra for different [C 16 ). As ionic strengths we have chosen low 0.7 mM and high 500 mM values for each surfactant mixing ratio.…”
Section: ■ Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Results and Discussion. In our procedure, we have recorded SFG spectra for different [C 16 ). As ionic strengths we have chosen low 0.7 mM and high 500 mM values for each surfactant mixing ratio.…”
Section: ■ Theorymentioning
confidence: 99%
“…However, for investigations of aqueous interfaces, there exist only a few experimental techniques that can probe their charging state and provide quantitative information on ϕ 0 . For solid/liquid interfaces, classical methods such as the surface-force apparatus and (colloidal probe) atomic force microscopy have been used to provide information on ϕ 0 by an analysis of force–distance curves and the application of the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory. For liquid/gas interfaces, the use of the thin-film pressure balance (TFPB) technique , is so far the only commonly accepted method for quantitative analysis but is also constrained to stable foam or emulsion thin films.…”
Section: Introductionmentioning
confidence: 99%
“…McLean et al (2005) reported that the Milner, Witten, and Cates (MWC) model (Milner et al, 1988) gives a better fitting than the AdG theory for the interaction between hydrophobic surfaces with adsorbed triblock copolymer layers, presumably because the segment density profile on the adsorbed polymer on the surfaces is in line with the assumptions of the MWC model. Further, it is theoretically and experimentally difficult to decouple steric forces from hydrodynamic forces associated with the expulsion of solvent during compression of a polymer brush or film (Wu et al, 2018). The steric force also acts between surfaces with adsorbed aggregate structures, such as micelles.…”
Section: Steric Forcementioning
confidence: 99%